The effect of curcumin on anthropometric indices, blood pressure, lipid profiles, fasting blood glucose, liver enzymes, fibrosis, and steatosis in non-alcoholic fatty livers - Safari, Zahra; Bagherniya, Mohammad; Khoram, Ziba; Ebrahimi Varzaneh, Amrollah; Heidari, Zahra; Sahebkar, Amirhossein; Askari, Gholamreza (Frontiers in Nutrition, 2023)
Background Non-alcoholic fatty liver disease (NAFLD) is the most common form of liver disease. Curcumin is a natural polyphenol that may be effective against liver steatosis and steatohepatitis. The present study aimed to evaluate the effects of phytosomal curcumin on lipid profile, fasting blood sugar, anthropometric indices, liver enzymes, fibrosis, and steatosis in non-alcoholic fatty liver patients. Methods The participants were randomized to the curcumin–phosphatidylserine phytosomal receiving group and the placebo receiving group and were followed up for 12 weeks. Data on anthropometric indices, lipid profile, blood glucose, blood pressure, liver enzymes, hepatic steatosis, and fibrosis were collected at the beginning and the end of the clinical trial. Results Supplementation for 12 weeks with phytosomal curcumin significantly reduced fibrosis and steatosis in the phytosomal curcumin receiving group compared with the placebo group (p < 0.05). Phytosomal curcumin also significantly reduced waist circumference and blood pressure compared with the placebo group (p < 0.05). There was no significant difference between the phytosomal curcumin and the placebo groups regarding changes in weight, body mass index, fasting blood glucose, liver enzymes, and lipid profile. Conclusion Curcumin, at a dose of 250 mg per day, might be effective in treating patients with NAFLD. Further studies are necessary to confirm these findings and to discover the underlying mechanisms. Clinical trial registration https://www.irct.ir/trial/43730, identifier: IRCT20121216011763N39.